Maxillary sinus detection on cone beam computed tomography images using ResNet and Swin Transformer-based UNet - Celebi, Adalet; Imak, Andac; Uzen, Huseyin; Budak, Umit; Turkoglu, Muammer; Hanbay, Davut; Sengur, Abdulkadir (Elsevier Science Inc, 2024)
Objectives. This study, which uses artificial intelligence-based methods, aimed to determine the limits of pathologic conditions and infections related to the maxillary sinus in cone beam computed tomography (CBCT) images to facilitate the work of dentists. Methods. A new UNet architecture based on a state-of-the-art Swin transformer called Res-Swin-UNet was developed to detect the sinus. The encoder part of the proposed network model consists of a pre-trained ResNet architecture, and the decoder part consists of Swin transformer blocks. Swin transformers achieve powerful global context properties with self-attention mechanisms. Because the output of the Swin transformer generates sectorized features, the patch expanding layer was used in this section instead of the traditional upsampling layer. In the last layer of the decoder, sinus diagnosis was conducted through classical convolution and sigmoid function. In experimental works, we used a data set including 298 CBCT images. Results. The Res-Swin-UNet model achieved more success, with a 91.72% F1-score, 99% accuracy, and 84.71% IoU, outperforming the state-of-the-art models. Conclusions. The deep learning-based model proposed in the present study can assist dentists in automatically detecting the boundaries of pathologic conditions and infections within the maxillary sinus based on CBCT images. (Oral Surg Oral Med Oral
Keywords: Convolutional Neural-Network; Active Contours; Classification; Segmentation; Recognition; Teeth